"No time to waste" in applying the lessons from Latin America's 50 years of housing policies. (April 2019) - Rojas, Eduardo
The United Nations' New Urban Agenda (NUA) calls for housing to play a prominent role in achieving more inclusive, safe, resilient and sustainable cities. Latin America offers more than 50 years of experience with housing policies: some successful, others failures. This paper reviews the lessons from this experience that can be of use for the rapidly urbanizing countries of sub-Saharan Africa and East Asia, as well as for the Latin American countries that are lagging behind in improving the housing conditions of their populations or not dealing effectively with the urban effects of their housing policies.